Implementation Of Shotgun Wedding In The Existence Of Gorontalo Customary Law - Rosmawati Sune (Universitas Negeri Gorontalo, 2020)
This study aims to determine the implemntation of a shoutgun wedding in the existence of Gorontalo customary law abd to determine the inhibiting factors for the implementation of shotgun wedding in Gorontalo customery law, Gorontalo Province. The method used in this research is empirical legal research with a social law research model whose research object is about people’s behavior. Sources of data used in this research are primary data that are obtained in the field and secondary data from books, periodicals, magazines, newspapers, documents, regulations, laws, etc. The population used by the researches is all shotgun wedding actors and customary leaders in Limehe Timur Village, Tabongo Sub-district, Gorontalo District. The data are collected trough interviews. The results show that the existence of Gorontalo customary law on the shotgun wedding are the behavior of the community, the economy, and the lack education regarding the values of customs, while the external inhibiting factors are government policies, natural conditions, and external cultural influences